First record of an Andricus oak gallwasp from the Oriental Region: a new species from Taiwan (Hymenoptera: Cynipidae: Cynipini) - Tang, Chang-Ti; Melika, George; Yang, Man-Miao; Nicholls, James; Csóka, György; Stone, Graham N. (Zootaxa, 2009)
A new species of oak gallwasp, Andricus formosanus is described from Taiwan which induces integral leaf galls on Quercus dentata (Section Quercus sensu stricto). The gall and adults of the new species most closely resembles Andricus moriokae Monzen, known from Japan. Data on the diagnosis, distribution and biology of the new species is given.